Model Pembelajaran Sorogan Dan Diskusi Dalam Meningkatkan Prestasi Belajar Membaca Kitab Santri Di Pondok Pesantren Al-Hidayah Tarik Sidoarjo - Asmawi Asmawi (Pena Islam Jurnal Pendidikan Agama Islam, 2022)
One of the many models including the sorogan and discussion model, this model is considered to be able to unite classical learning activities with modern contemporary learning models. Therefore, this model is considered to be able to increase the intensity of students' learning achievements, especially in terms of reading books. The influence of the simultaneous sorogan learning model and discussion in improving the learning achievement of the students of Al-Hidayah Tarik Sidoarjo Islamic Boarding School. This type of research is quantitative associative. Second, the discussion learning model has also been implemented at Al-Hidayah Tarik Islamic Boarding School in Sidoarjo. Third, the sorogan learning model and discussion are very useful in improving students' learning achievement in reading books at Al-Hidayah Tarik Sidoarjo Islamic Boarding School. Based on the results of data analysis, it is known that hypothesis testing shows that: first, there is an influence of the Sorogan Learning Model in Improving Student Achievement in Reading Books of Santri at Al-Hidayah Tarik Islamic Boarding School, Sidoarjo.